Applications and Topics of Physics in Surgery (Alternate Horizons, 2023)
Physics has many applications in medicine and surgery, it has allowed new ways of curing a patient and, in some cases, has replaced surgery altogether. This essay will discuss various topics, procedures and innovations in surgery that require physics.
Keywords: Physics; Surgery; Medical physics; Medicine; Imaging; Electromagnetic spectrum; Nuclear medicine